Effects of sex steroid hormones on sertoli cells metabolic pathways - Martins, Ana Catarina Dias (2013)
Developing germ cells use lactate, derived from glucose metabolism of Sertoli cells (SCs), as their main energy source. Androgens and estrogens have been implicated in the modulation of testicular cells energy metabolism, particularly in SCs. The goal of the present study was to shed light on the effects of sex steroid hormones on glucose metabolic pathways in rat SCs. The mRNA levels of glucose transporters 1 and 3 (GLUT1 and GLUT3), phosphofructokinase 1 (PFK1) and lactate dehydrogenase chain C (LHD C) were analyzed by RT-PCR, and protein levels of GLUTs, PFK1, LDH and monocarboxylate transporter 4 (MCT4) were analyzed by Western Blot, in enriched primary cultures of immature rat SCs treated with 17β-estradiol (E2) or 5α-dihydrotestosterone (DHT). Our results show that both E2 and DHT downregulated the gene transcript levels of PFK-1, GLUT1 and GLUT3. However, only DHT-treated cells presented a downregulation of LDH C gene transcript levels. Interestingly, the protein levels of these enzymes and transporters remained unaltered except in DHT-treated cells that presented a significant decrease on GLUT1 protein levels evidencing a possible pathway for the regulation of glucose metabolism in SCs by androgens. Taken together, these results demonstrated a relationship between the action of sex steroid hormones and energy metabolism of SCs, providing evidences for the mechanisms by which E2 and DHT exert their function as modulators of rat SCs glucose metabolism.